SHORTCOMINGS IN THE METHODOLOGY FOR INVESTIGATING OFFENSES RELATED TO HIGH TREASON AND COLLABORATION IN UNCONTROLLED TERRITORIES - Bondarenko, Olena; Levchenko, Anzhelika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the purpose of this article is to investigate and analyze the shortcomings of the methodology for investigating offenses related to high treason and collaboration in the uncontrolled territories. Research methods: the following methods were used in the course of the work, namely: information and analytical, which analyzed the public activities of persons suspected of collaboration, as well as events taking place in the occupied territories to identify patterns and factors indicating their involvement. These include psychological methods - the study of social conditions under which individuals may begin to cooperate with the aggressor, technical methods, including the analysis of digital evidence, and others. Results: this article focuses on clarifying such concepts as collaboration, high treason, which is currently one of the most pressing problems of our country, as well as counteracting this negative offense. The author also examines the shortcomings of the methodology for investigating these offenses. Investigation of offenses related to treason and collaboration in uncontrolled territories is one of the most difficult and painful topics in law enforcement, especially in the context of modern geopolitical conflicts. Ukraine, as a country that has become a victim of aggression and occupation of part of its territory, is no exception, so collaboration and treason during the war are one of the main threats to national security and violation of international norms. And this is not only a moral but also a legal problem today, which poses numerous challenges to law enforcement agencies and the judiciary. These challenges include the complexity of the evidence base, the need to adapt legislation to new realities, and pressure from the public, which has high expectations of the effectiveness of the fight against collaboration and treason. It is also worth noting that the investigation of such offenses often faces difficult legal and practical problems. This is especially true in the territories controlled by the occupation forces or that have suffered significant damage as a result of hostilities. And in a time of war, it is impossible to conduct standard investigative actions such as searches and interrogations, which greatly complicates the investigation of these offenses. Discussion: the difficulties and shortcomings in the fight against collaboration and treason, especially in the context of war and occupation, are analyzed. Attention is paid to the problems of collaborationism in Ukraine, in particular in the occupied territories, where it has many aspects: moral, legal and social, because it is not only an offense against the state, but also a deep social problem that leads to the division of society, destroys trust in the government and undermines state sovereignty.